2023
DOI: 10.20448/jeelr.v10i2.4564
|View full text |Cite
|
Sign up to set email alerts
|

The preschool teachers' perspective of digital technology use in classrooms: A case study of North Maluku province, Indonesia

Abstract: The significance of information and communication technologies in the educational sector in the last few decades has tremendously increased. The current study aims to examine the significance of various individual factors such as teachers' self-concept, self-efficacy and ICT-related subjective self in predicting their perceptions of ICT usability leading to enhance preschool children’s learning outcomes. To achieve the study objectives, the authors applied a quantitative research methodology. After surveying 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In general, external circumstances can also be a catalyst for the use of digital technologies. A study by Ismail (2023) confirms that COVID-19 has triggered an increased need and willingness to introduce digital technologies into kindergartens. In the Czech Republic, recent could also play a role in financial support from the Ministry of Education towards digitization, which has helped schools to expand and possibly add new equipment of their choice.…”
Section: Discussion and Conclussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In general, external circumstances can also be a catalyst for the use of digital technologies. A study by Ismail (2023) confirms that COVID-19 has triggered an increased need and willingness to introduce digital technologies into kindergartens. In the Czech Republic, recent could also play a role in financial support from the Ministry of Education towards digitization, which has helped schools to expand and possibly add new equipment of their choice.…”
Section: Discussion and Conclussionmentioning
confidence: 91%
“…In a Jordanian study, Alomyan and Alelaimat (2021) showed that digital technologies are more willingly used by teachers who have a higher education (teachers with a bachelor's degree use it more often than teachers without a degree) and a sense of their own competence. An Indonesian study by Ismail (2023) clarifies that the combination of a teacher's self-concept, self-efficacy, and ICT-related subjective self is a reliable predictor of digital technology use in kindergarten.…”
Section: Discussion and Conclussionmentioning
confidence: 99%